Polyfunctional CD4 T-cells correlate with in vitro mycobacterial growth inhibition following Mycobacterium bovis BCG-vaccination of infants. Issue 44 (17th October 2016) - Smith, Steven G.; Zelmer, Andrea; Blitz, Rose; Fletcher, Helen A.; Dockrell, Hazel M.
Highlights: BCG vaccination induces predominantly polyfunctional CD4 T-cells in infants. BCG vaccination induces Th-17 response in infants. Capacity of PBMC to inhibit mycobacterial growth in vitro enhanced after BCG. Correlation between polyfunctional T-cells and growth inhibition after BCG. Abstract: Background: Vaccination with Bacillus Calmette Guerin (BCG) protects infants against childhood tuberculosis however the immune mechanisms involved are not well understood. Further elucidation of the infant immune response to BCG will aid with the identification of immune correlates of protection against tuberculosis and with the design of new improved vaccines. The purpose of this study was to investigate BCG-induced CD4+ T-cell responses in blood samples from infants for cytokine secretion profiles thought to be important for protection against tuberculosis and compare these to PBMC-mediated in vitro mycobacterial growth inhibition. Methods: Blood from BCG-vaccinated or unvaccinated infants was stimulated overnight with Mycobacterium tuberculosis ( M. tb ) purified protein derivative (PPD) or controls and intracellular cytokine staining and flow cytometry used to measure CD4+ T-cell responses. PBMC cryopreserved at the time of sample collection were thawed and incubated with live BCG for four days following which inhibition of BCG growth was determined. Results: PPD-specific IFNγ+TNFα+IL-2+CD4+ T-cells represented the dominant T-cell response at 4 months and 1 year after infant BCG. These responses were undetectable in age-matched unvaccinated infants. IL-17+ CD4+ T-cells were significantly more frequent in vaccinated infants at 4 months but not at 1-year post-BCG. PBMC-mediated inhibition of mycobacterial growth was significantly enhanced at 4 months post-BCG as compared to unvaccinated controls. In an analysis of all samples with both datasets available, mycobacterial growth inhibition correlated significantly with the frequency of polyfunctional (IFNγ+TNFα+IL-2+) CD4+ T-cells. Conclusions: These data suggest that BCG vaccination of infants induces specific polyfunctional T-helper-1 and T-helper-17 responses and the ability, in the PBMC compartment, to inhibit the growth of mycobacteria in vitro. We also demonstrate that polyfunctional T-helper-1 cells may play a role in growth inhibition as evidenced by a significant correlation between the two.